Are Autonomously Motivated University Instructors More Autonomy-Supportive Teachers? - Maï Yasué; Lucas Jeno; Jody Langdon (International Journal for the Scholarship of Teaching and Learning, 2019)
We extended the research on autonomy-supportive teaching to universities and examined the relationships between autonomous motivation to teach and autonomy-supportive teaching. Autonomously motivated university instructors were more autonomy-supportive instructors. The freedom to make pedagogical decisions was negatively correlated with external motivation towards teaching. Participants indicated that large class sizes, high teaching loads, publication pressures, and a culture that undervalues effective undergraduate teaching undermined both student learning and their feelings of autonomy. Together these results presents a picture of a subset of university instructors who remained autonomously motivated to teach, irrespective of barriers they experienced from university administrators or policies.